Differences in land cover – biodiversity relationships complicate the assignment of conservation values in human-used landscapes. (July 2018) - Nopper, Joachim; Riemann, Jana C.; Brinkmann, Katja; Rödel, Mark-Oliver; Ganzhorn, Jörg U.
Highlights: Alpha diversity of reptiles declines from intact to altered habitats. Alpha diversity of reptiles drops drastically below a vegetation cover of 10–30%. Declines of alpha diversity differ depending on life-history traits of the species. Minimum 30% vegetation cover at the local scale maintains relatively high diversity. A mosaic of different land cover types may promote biodiversity conservation. Abstract: The anthropogenic conversion of natural landscapes continues to be a severe threat to biodiversity. As humans depend on these natural landscapes for sustainable resource provisioning as well, the conversion likewise affects biodiversity and people's livelihoods. To identify options for reconciling human needs and biodiversity conservation we studied the relationship of land use and reptile diversity. In a dryland in southwestern Madagascar, we compared reptile diversity between five land-cover classes and identified trait-dependent effects of land use on reptiles with regard to substrate preference and activity phase. Thresholds of diversity declines were detected at the transition from intact forest towards land-cover types with reduced forest cover, and at the transition to habitats with a woody plant cover below 10–30%. Community equitability increased towards lower vegetation cover. With increasing habitat openness, rare species were lost and a small subset of similarly successful degradation-tolerant species remained. Land cover – biodiversity relationships varied considerably between reptile assemblages that differed in activity phases. Nocturnal reptiles were more strongly affected by habitat conversion than diurnal reptiles. Substrate preference did not determine degradation tolerance. These findings provide important implications for conservation planning in drylands. For many species converted habitats can still be suitable. However, ignoring the fine-scale habitat requirements of animals will likely lead to imprecise conclusions on the conservation value of converted drylands.